If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-7)-3(x+2)+4(x +1)-2=0
We simplify the equation to the form, which is simple to understand
2(x-7)-3(x+2)+4(x+1)-2=0
Reorder the terms in parentheses
+(+2x-14)-3*(x+2)+4*(x+1)-2=0
Remove unnecessary parentheses
+2x-14-3+*(+x+2+)+4+*(+x+1+)-2=0
Reorder the terms in parentheses
+2x-14+(-3x-6)+4*(x+1)-2=0
Remove unnecessary parentheses
+2x-14-3x-6+4+*(+x+1+)-2=0
Reorder the terms in parentheses
+2x-14-3x-6+(+4x+4)-2=0
Remove unnecessary parentheses
+2x-14-3x-6+4x+4-2=0
We move all terms containing x to the left and all other terms to the right.
+2x-3x+4x=0+14+6-4+2
We simplify left and right side of the equation.
+3x=+18
We divide both sides of the equation by 3 to get x.
x=6
| 7a=4a-9 | | 2x^2-(4-x^2)=6x-4 | | 12z+4=2(2x-7) | | (4x-4/x-7)(3x+5/x-1) | | 5n=53.2-2.6n | | 10+.06x=0 | | 11=7+4w | | 7y+8/2=4 | | 60+60+x+x=360 | | -8+4v=16 | | 60+60+x+x= | | 4+4-e=2 | | 68+65+x+x= | | 5x+5=10x-3 | | -10x^2+50x+12=0 | | 3n+5x=6 | | .5(8*12)= | | 1/2(2x-5)=3 | | .5(10*12.8)= | | -16X^2+4X+20=0 | | 14x+35=(4x-9)-x | | 10(12.8)= | | 4x+28=13x-93 | | 11x-11=100 | | 9(t+1)=81 | | 3(H+5)=22 | | -2=v-6+3 | | 7x+8/2+4x-3/6=34 | | 0=(1/5)x+2 | | e-5+7=2 | | e/5+7=4 | | 16+3/4x=7 |